DIRECT EVIDENCE OF FLUID MIXING IN THE FORMATION OF STRATABOUND PB-ZN-BA-F MINERALISATION IN THE ALSTON BLOCK, NORTH PENNINE OREFIELD (ENGLAND) - Bouch J.E.; Naden J.; McKervey J.A.; Benham A.J.; Shepherd T.J.; Young B.; Sloane H.J. (My University, 2006)
The North Pennine Orefield Alston Block has produced approximately 4 Mt Pb, 0.3 Mt Zn, 2.1 Mt fluorite, 1.5 Mt barite, 1 Mt witherite, plus a substantial amount of iron ore and copper ore from predominantly vein-hosted mineralisation in Carboniferous limestones. However, a significant proportion of this production (ca. 20%) came from stratabound deposits. Though much is known about the vein mineralisation, the relationship between the veins and the stratabound mineralisation is not well-understood. New petrographic, isotopic and fluid inclusion data derived from samples of stratabound mineralisation allow us to present a unified model that addresses the genesis of both the vein and stratabound styles of mineralisation. The mineralisation can be considered in terms of three episodes: 1. Dolomitisation and ankeritisation Limestones in the vicinity of the stratabound mineralisation were pervasively dolomitised/ankeritised, and developed vuggy porosity in the presence of a high-salinity brine consistent with fluids derived from adjacent mud and shale-filled basins. 2. Main stage fluorite quartz sulphide mineralisation Metasomatism of limestone was accompanied by brecciation, dissolution and hydrothermal karstification with modification of the existing pore system. The open space was filled with fluorite, galena, sphalerite, quartz and barite, formed in response to mixing of low-salinity sodic groundwater with high-salinity calcic brine with elevated metal contents (particularly Fe up to 7,000 ppm) relative to normal high total dissolved solids sedimentary brines. 3. Late stage barite mineralisation paragenetically appears to represent either the waning stages or the distal portions of the main hydrothermal circulation system under cooler conditions. © British Geological Survey 2006.
Keywords: ALSTON BLOCK; NORTH PENNINE OREFIELD; STRATABOUND MINERALISATION; Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная